(untitled) (Syariati: Jurnal Studi Al-Qur’an dan Hukum, 2020)
In recent years Islamic financial institution industry is developing so rapidly, as weel as Islamic banking in Indonesia which is developing significantly. The development of Islamic banking must be accompanied by good governance sothat sharia is not only tag line for the Islamic financial institutions. SOP of Islamic banking must be carried out correctly based on sharia principles. Therefore, Bank Indonesia issued Bank Indonesia Regulation No. 11/33 / PBI 2009 concerning the implementation of Good Corporate Governance (GCG) for Sharia Commercial Banks and Sharia Business Units. The five principles are: Transparency, Accountability, Responsibility, Professional and Fairness or equity. Good Corporate Governance (GCG) is a banking management system designed to improve compliance with laws and regulations of applicable moral ethics. According to Chapra the application of Good Corporate Governance is a requirement for Islamic banks to develop well and healthily. The implementation of Good Corporate Governance (GCG) in Islamic banking is expected to create a healthy, conducive, transparent and efficient business.